2021
DOI: 10.3390/membranes11020076
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Biofouling Potential in SWRO Plants with a Flow-Cytometry-Based Bacterial Growth Potential Method

Abstract: Measuring the bacterial growth potential of seawater reverse osmosis (SWRO) feed water is an issue that is receiving growing attention. This study developed and demonstrated the applicability of the flow-cytometry (FCM)-based bacterial growth potential (BGP) method to assess the biofouling potential in SWRO systems using natural microbial consortium. This method is relatively fast (2–3 days) compared to conventional bioassays. The effect of the potential introduction of nutrients during measurement has been st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Low alginate concentrations (25 mg/L) limited NF/RO fouling, but high concentrations (100 mg/L) appeared to promote calcite scaling. Dhakal et al [39] developed and demonstrated the applicability of the flow cytometry (FCM)-based bacterial growth potential (BGP) method to assess the biofouling potential in seawater (SW) RO systems using a natural microbial consortium. Sperle et al [40] reported the potential of UVC irradiation using the recently developed UV-LEDs as an in situ pretreatment strategy for biofouling control in RO or NF systems.…”
Section: Conventional Thermal Technologiesmentioning
confidence: 99%
“…Low alginate concentrations (25 mg/L) limited NF/RO fouling, but high concentrations (100 mg/L) appeared to promote calcite scaling. Dhakal et al [39] developed and demonstrated the applicability of the flow cytometry (FCM)-based bacterial growth potential (BGP) method to assess the biofouling potential in seawater (SW) RO systems using a natural microbial consortium. Sperle et al [40] reported the potential of UVC irradiation using the recently developed UV-LEDs as an in situ pretreatment strategy for biofouling control in RO or NF systems.…”
Section: Conventional Thermal Technologiesmentioning
confidence: 99%
“…Fluorescence intensity was collected at FL1 = 533 ± 30 nm, FL3 > 670 nm, with sideward-and forward-scattered light intensities also being obtained. All data were processed with the BD Accuri CFlow ® software [46,47]. Electronic gating was used to select SYBR green-labeled signals to quantify the total bacterial cell count following the procedure described by Hammes and Egli, (2005) [48].…”
Section: Total Cell Countmentioning
confidence: 99%
“…However, a significant obstacle to the high performance of RO technology is membrane biofouling, which impacts the water flux and the lifetime of membrane filters and modules [ 1 , 2 , 3 , 4 , 5 ]. Recently, several methods have been developed to monitor biofouling in RO systems, such as assimilable organic carbon (AOC), the membrane biofilm formation rate (mBFR) and bacterial growth potential (BGP) [ 6 , 7 ]. Many pretreatment processes have also been employed to decrease the fouling of RO membranes, such as the chlorination of feed water, ultrafiltration and microfiltration [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%